Exposure and lighting for digital photographers only - Meadhra, Michael; Lowrie, Charlotte K. (Wiley, 2007)
The authors give readers a deeper understanding of exposure and lighting and the ability to apply that knowledge to achieve real creative control over their digital photograpy.